Cover Feature: Hollow Spheres Consisting of SnS Nanosheets Conformally Coated with S‐Doped Carbon for Advanced Lithium‐/Sodium‐Ion Battery Anodes (ChemElectroChem 4/2020). Issue 4 (31st January 2020) - Guo, Weiyuan; Ding, Kang; Mei, Shixiong; Li, Xingxing; Feng, Xiaoyu; Guo, Siguang; Fu, Jijiang; Zhang, Xuming; Gao, Biao; Huo, Kaifu; Chu, Paul K.
Abstract : The Cover Feature shows that hollow spheres assembled with carbon‐coated SnS nanosheets can effectively promote the transmission and storage of lithium/sodium ions. More information can be found in the Article by W. Guo et al. on page 914 in Issue 4, 2020 (DOI: 10.1002/celc.201901923 ).